2008
DOI: 10.1021/ja806283e
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis of All Phosphatidylinositol Mannoside (PIM) Glycans from Mycobacterium tuberculosis

Abstract: The emergence of multidrug-resistant tuberculosis (TB) and problems with the BCG tuberculosis vaccine to protect humans against TB have prompted investigations into alternative approaches to combat this disease by exploring novel bacterial drug targets and vaccines. Phosphatidylinositol mannosides (PIMs) are biologically important glycoconjugates and represent common essential precursors of more complex mycobacterial cell wall glycolipids including lipomannan (LM), lipoarabinomannan (LAM), and mannan capped li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 52 publications
4
73
1
Order By: Relevance
“…We have no ready explanation for the difference in outcome; however, we do note that the magnitude of the binding of PIMs to DC-SIGN reported in the study by Torrelles et al was very small for all of the species tested and thus lacked specificity. Our data are more in agreement with a recent study by Boonyarattanakalin and coworkers (12). This study on the chemical synthesis of PIMs showed a high affinity of DC-SIGN for the polar PIMs, i.e., PIM 5 and PIM 6 , and low or no affinity for the less mannosylated PIMs, i.e., PIM 2 and PIM 4 , respectively, in a fluorescence scanning assay of a PIM microarray.…”
Section: Discussionsupporting
confidence: 93%
“…We have no ready explanation for the difference in outcome; however, we do note that the magnitude of the binding of PIMs to DC-SIGN reported in the study by Torrelles et al was very small for all of the species tested and thus lacked specificity. Our data are more in agreement with a recent study by Boonyarattanakalin and coworkers (12). This study on the chemical synthesis of PIMs showed a high affinity of DC-SIGN for the polar PIMs, i.e., PIM 5 and PIM 6 , and low or no affinity for the less mannosylated PIMs, i.e., PIM 2 and PIM 4 , respectively, in a fluorescence scanning assay of a PIM microarray.…”
Section: Discussionsupporting
confidence: 93%
“…In particular, the higher-order PIMs (PIM 5 and PIM 6 ), with terminal α(1→2)-linked Man p residues reminiscent of the mannose cap of Man-LAM, were of interest. As expected, DC-SIGN recognizes the higher-order PIMs with high affinity as compared with the lower-order PIMs (Boonyarattanakalin et al , 2008; Driessen et al , 2009;). Besides PIMs, other potential ligands in the mycobacterial cell wall for DC-SIGN have been identified: lipomannan, Man-AM and mannosylated lipoproteins 19 and 45 kDa (Pitarque et al , 2005), and more recently, capsular α-glucan (Geurtsen et al , 2009) (a list is provided in Table 3).…”
Section: Part II – Interactions With Host Immune Systemsupporting
confidence: 80%
“…Highest MALDI mass = 7785 (Joe, et al, 2007) (Vasan, et al, 2007) Nonasaccharide subunits of the atypical O-antigen polysaccharide from Helicobacter pylori strains TOF Synthesis by dimerization and trimerization of suitably protected trisaccharide repeating unit (Fulse, et al, 2007) Pentasaccharide repeat from Phosphatidylinositol mannosides (PIMs) from Mycobacterium tuberculosis TOF Synthesis of all PIMs including phosphatidylinositol (PI) and phosphatidylinositol mono-to hexamannosides (PIM 1 to PIM 6 ) (Boonyarattanakalin, et al, 2008) Spore-surface pentasaccharide from Bacillus anthracis Solid-phase synthesis MALDI (Werz, et al, 2007a Tetra-acylated lipid A derivatives from Porphyromonas gingivalis…”
Section: Cd52 Antigenmentioning
confidence: 99%